1999
DOI: 10.1046/j.1463-5224.1999.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of preserved equine renal capsule to repair lamellar corneal lesions in normal dogs

Abstract: The purpose of this study was to evaluate the use of equine renal capsule preserved in 98% glycerine to repair lamellar corneal lesions in normal dogs. For this purpose, 12 dogs, divided into six groups (n = 2), were used to evaluate the 1st to 7th day, 15th day and 30th to 60th postoperative day. In order to perform the histologic study, the clinical procedures were analyzed, while the recipient's corneas were collected. The photophobia and blepharospasm also were more intense in the 1st to 7th postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 7 publications
1
53
0
9
Order By: Relevance
“…Our results showed that photophobia/blepharospasm/epiphora were significant in the early period after surgery (3) , and may be due to the scleral edema stimulating the scleral nerves and the sutures stimulating the conjunctival eyelid. Sutures were not removed to avoid additional maneuvres that could possibly interfere in the surgical site.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Our results showed that photophobia/blepharospasm/epiphora were significant in the early period after surgery (3) , and may be due to the scleral edema stimulating the scleral nerves and the sutures stimulating the conjunctival eyelid. Sutures were not removed to avoid additional maneuvres that could possibly interfere in the surgical site.…”
Section: Discussionmentioning
confidence: 66%
“…Many methods have been described for repair of deep corneal ulcers and perforations, and yet, with the exception of penetrating keratoplasties with autogenous grafts, corneal opacification may be the final result (3) . In humans, biological prosthesis can be performed by reconstructing the anterior ocular segment (5,15) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations